Rancang Bangun Sistem Informasi Persediaan Pakan Ternak Berbasis Website di Koperasi Serba Usaha Tandangsari Sumedang - Sarah Ayu Nur Sawitri; Nova Indrayana Yusman Yusman; Partono Partono (Ma'soem University, 2021)
Tandangsari Multipurpose Cooperative is a cooperative that develops community businesses in the field of dairy farming, savings and loan cooperatives and animal feed. In the processing of animal feed supplies, this cooperative is still based on semi-computerization. So cooperatives need optimal programs to improve their performance. The design of the inventory information system is a system that will be built to reduce the problems contained in the previous livestock feed inventory information system. Loss and corruption of some data that prevents data from being inputted. The method used in this animal feed inventory information system is object orientation (OOAD) and uses the Rational Unified Process (RUP) model and is supported by the Unified Modeling Language (UML) for software engineering processes with a good structure. The author draws the conclusion that the system in this design can be useful and light in the inventory process and is able to solve problems that occur so that the system that is run can be used anytime and anywhere.